Conceptual foundations of managing the investment potential of non-bank financial institutions - Cherniavskyi , Heorhii (Ways to Improve Construction Efficiency, 2025)
The article substantiates the conceptual foundations of managing the investment potential of non-bank financial institutions under the current transformation of the financial market. The investment potential of NBFIs is interpreted as an integrated ability to accumulate, transform and allocate financial resources with due regard to profitability, liquidity, risk, solvency and regulatory compliance. The methodology combines the systems approach, institutional and functional analysis, content analysis of scientific publications, comparative analysis of the legal framework and generalisation of empirical data from the National Bank of Ukraine on the performance of the non-bank sector. The paper clarifies the economic content of the categories “investment potential of NBFIs” and “management of the investment potential of NBFIs”, identifies the key components of such potential and substantiates the logic of their managerial interaction. Using official NBU data for the fourth quarter of 2025, the paper shows that the Ukrainian non-bank sector is markedly asymmetric: the assets of financial companies and insurers increased, whereas the assets of credit unions and pawnshops decreased. This confirms that the management of investment potential should be segment-specific rather than uniform across the entire sector. The scientific novelty consists in clarifying the conceptual content of managing the investment potential of NBFIs as a systemic process aimed at the formation, mobilisation, allocation, monitoring and adjustment of investment resources; in developing an authorial conceptual model that integrates target, resource, process and functional, analytical and risk, and result blocks; and in substantiating the link between the segment structure of the non-bank market, the character of the resource base and the features of investment strategy. The practical significance of the results lies in their applicability to the further assessment of the investment potential of NBFIs, the improvement of investment management mechanisms, the development of performance indicators, investment budgeting tools and early warning systems for investment risks.